From the Social Gospel to "the Plain Bread of Leninism": A.E. Smith's Journey to the Left in the Epoch of Reaction After World War I - Mitchell, Tom (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1994)
A.E. Smith was a central figure in the Communist Party from the mid-1920s until his death in 1947. An advocate of the radical Social Gospel until at least 1923, Smith's interchange with leading members of the Canadian Communist movement, the growing prestige of the Soviet State, and his disillusionment with the social democratic movement in Canada and abroad, combined during the post-war epoch of reaction to cause a shift in his perspective away from the optimistic verities of the Social Gospel to his apocalyptic vision of the Communist International. While he retained his basic epistemological perspective after 1923, Smith's estrangement from the non-Communist left led to his political isolation and, in early 1925, to his entry into the Communist Party.